Comparing the Effectiveness of Child-Centered Play Therapy and Story Therapy on Social Skills and Shyness in Preschool Children with Attention Deficit Hyperactivity Disorder in Tehran - Azin Soroushvala; Alireza Merati; Mehdi Yousefvand (Iranian Journal of Educational Research)
Objective: The aim of this study was to compare the effectiveness of child-centered play therapy and story therapy on social skills and shyness in preschool children with attention deficit hyperactivity disorder in Tehran. Methods: The research method was a semi-experimental pre-test-post-test design with experimental and control groups. The statistical population of this research included all preschool children in 22 districts of Tehran, who were selected from three districts 1, 3, and 6 using purposive sampling, and 5 preschool centers were selected from these three districts. The selection of the research sample was done in two stages. In the first stage, 80 children were examined with a research checklist, and in the second stage, 45 children with a primary diagnosis of attention-deficit-hyperactivity disorder were selected, who were normal in terms of motor function and free of other psychological disorders, and to differentiate normal children and children with Attention-deficit-hyperactivity disorder, they were evaluated with behavioral inventory and clinical interview for more certainty. Then these people were compared in terms of age, gender, IQ and socio-economic status. To collect research data, social skills questionnaire - parent form (Gresham and Elliott, 1990) and shyness test (Cheek and Briggs, 1990) were used. Therapeutic interventions were also implemented with the protocols of story therapy (Sabri and Vakili, 2013) and child-centered play therapy (Qureishi, 2015). Results: The results showed that in terms of social skills, the therapeutic approach of story therapy has obtained better results, whereas, play therapy has more significant effects on shyness. Conclusions: The findings of the research can be a practical guide for therapists and psychologists in the field of children psychology.